2004
DOI: 10.1016/s1570-0232(04)00602-6
|View full text |Cite
|
Sign up to set email alerts
|

Determination of glimepiride in human plasma using semi-microbore high performance liquid chromatography with column-switching

Abstract: A fully automated semi-microbore high performance liquid chromatographic (HPLC) method with column-switching using UV detection was developed for the determination of glimepiride from human plasma samples. Plasma sample (900 microl) was deproteinated and extracted with ethanol and acetonitrile. The extract (70 microl) was directly injected into a Capcell Pak MF Ph-1 pre-column where the primary separation occurred to remove proteins and retain drugs using a mixture of acetonitrile and 10mM phosphate buffer (pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The lack of interference with other peaks at the retention time of glimepiride, when blank serum samples were tested, supported the specificity of the method. According to the literature 18,19 the sensitivity of the HPLC method applied in this study (LLOQ, 0.01 µg/ml) was comparable to that of HPLC methodologies used by other investigators to determine concentrations of glimepiride. As expected, however, the HPLC method we used was less sensitive compared with HPLC coupled to tandem mass spectrometry 20,21 .…”
Section: Discussionsupporting
confidence: 64%
“…The lack of interference with other peaks at the retention time of glimepiride, when blank serum samples were tested, supported the specificity of the method. According to the literature 18,19 the sensitivity of the HPLC method applied in this study (LLOQ, 0.01 µg/ml) was comparable to that of HPLC methodologies used by other investigators to determine concentrations of glimepiride. As expected, however, the HPLC method we used was less sensitive compared with HPLC coupled to tandem mass spectrometry 20,21 .…”
Section: Discussionsupporting
confidence: 64%
“…One study was found describing the determination of glimepiride (GM) in plasma using column-switching with RAM column. The total time spent to determine only one sulfonylurea was 40 minutes (24). In this context, the present study describes the optimization of a rapid and simple method, using a column-switching HPLC with RAM column (sample preparation) and fused core column (analytical separation), for the simultaneous determination of three sulfonylureas: glibenclamide (GB), GM and gliclazide (GZ), in human plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the therapeutic important and clinical success of RSG and GLM, several methods have been developed for its quantitative determination in plasma samples and in pharmaceutical preparations. These methods for RSG alone include high performance liquid chromatography (HPLC),15–19 liquid chromatography‐tandem mass spectrometry (LC‐MS/MS),20 capillary electrophoresis,21 high performance tin layer chromatography (HPTLC),22, 23 or in combination with other anti‐diabetic drugs,24–29 and for GLM alone include derivative spectrophotometric technique,30 HPLC,31–33 LC‐MS/MS,34–37 or in combination with other anti‐diabetic drugs 38–41. A literature survey revealed that only one spectrophotometric estimation of RSG and GLM in tablet dosage form has been reported 42.…”
Section: Introductionmentioning
confidence: 99%